Multiple high-risk fertility behaviours and children under five mortality survivors among ever-married women of reproductive age in Nigeria - Obasanjo Afolabi Bolarinwa; Julia Marie Hajjar; Oluwatobi Abel Alawode; Kobi V. Ajayi; Adedoyin Tinuoya Roberts; Sanni Yaya (BMC, 2023)
Abstract Background Multiple high-risk fertility behaviours (MHRFBs), including maternal age < 18 or > 34 years old, a birth order 4+, and birth spacing < 24 months, can directly or indirectly affect survival outcomes among under-five children. There is a dearth of available information and data about these two phenomena in Nigeria. Thus, this study evaluates the prevalence of MHRFBs and examines the association between MHRFBs and under-five mortality survival (U5M) outcomes among ever-married women of reproductive age in Nigeria. Methods This study used the recent secondary datasets from the Nigerian Demographic Health Surveys conducted in 2018, with a total sample size of 10,304 women of reproductive age. The outcome variable was MHRFBs. Multivariable logistic regression analysis was employed to examine the association between U5M and MHRFBs. Odds ratios with a p-value of less than 0.05 were considered significant. Results It was found that among women who had MHRFBs, U5M was prevalent, particularly in young maternal age (< 18 years) and within short birth intervals (< 24 months). The adjusted odds ratio of the association between MHRFBs and U5M shows the experience of MHRFBs, in addition to other factors such as household wealth index, type of marriage, and sex of child, to be significant predictors for U5M. The odds were higher for U5M to occur among women who had experienced MHRFBs compared to those who have not had an experience of MHRFBs [aOR = 1.48; 95%CI: 1.02-2.17 ]. Similarly, the odds of U5M occurrence among women in polygamous marriages are higher compared to those in monogamous unions [aOR = 1.35; 95% CI: 1.10-1.65]. While under-five children born in the richest households (wealth quintiles) are less likely to die compared to those born in the poorest households [aOR = 0.64; 95% CI: 0.41-1.01]. Conclusion This study concludes that women in Nigeria who engaged in MHRFBs, particularly maternal ages < 18 years and short birth intervals (< 24 months), were more likely to experience U5M. Furthermore, children born to women who received post-natal care after delivery were more likely to survive U5M, as were children born to women with educated partners. We recommend strengthening educational opportunities and creating adaptive reproductive health education programs for ever-married women of reproductive age in Nigeria.